Pengaruh penerapan metode role playing terhadap keterampilan sosial dan kemampuan berpikir analitis siswa pada pembelajaran IPS - Yeni Puspitasari; Sapriya Sapriya (Universitas Pendidikan Indonesia, 2019)
Social and analytical thinking skill are highly essential to help students to communicate with their surroundings and help students to solve problems which correlate with their lives. The purpose of this study was to determine the effect of the use role playing method to social skills and analytical thinking of students at a public elementary school in Karawang. The method used is quasi-experimental with Nonequivalent Control Group Design (NCGD). The learning process taken in control group was through conventional learning and in experimental group was through role playing method. The results showed that there is improvement on students' social and analytical thinking skills after learning through role playing was implemented. T-test results between t-compared to the calculation result of t-observed that has been showed that t-observed < t-critical or Ho is rejected. It means there is a significant difference in the improvement of students' social and analytical thinking skills between who were taught by using role playing method and who were taught by using conventional learning. Furthermore, students' responses to the use of role playing method is positive. Students felt more involved in the learning process and not bored so that the lesson given can improve social and analytical thinking skills of students.